Conbercept for Treatment of Neovascular Age-Related Macular Degeneration and Visual Impairment due to Diabetic Macular Edema or Pathologic Myopia Choroidal Neovascularization: A Systematic Review and Meta-Analysis - Zhou, Pengxiang; Zheng, Siqian; Wang, Ente; Men, Peng; Zhai, Suodi (Frontiers in Pharmacology, 2021)
Background: Conbercept is a new anti-vascular endothelial growth factor (VEGF) drug. Here, we systematically conducted the efficacy, safety, compliance, and pharmacoeconomic evaluation of intravitreal conbercept (IVC) compared with other treatments in patients with neovascular age-related macular degeneration (nAMD), diabetic macular edema (DME) or pathologic myopia choroidal neovascularization (pmCNV). Methods Databases of PubMed, Embase, Cochrane Library, ClinicalTrials.gov, SinoMed, China National Knowledge Infrastructure and WanFang Data were systematically searched from the inception to Jul 27, 2021. Randomized clinical trials and pharmacoeconomic studies comparing IVC with control groups in adults with nAMD, DME or pmCNV were reviewed and selected. Meta-analyses were performed using the fixed-effects model when pooled data were homogeneous. Heterogeneous data were analysed using the random-effects model. Primary outcomes included visual improvement rate, mean change in visual acuity or best corrected visual acuity, and pharmacoeconomic outcomes. Additional outcomes were the mean change in fundus examination values, adverse events (AEs), quality-of-life measures and number of injections. Results Among 3,360 screened papers, 22 original studies with 1,910 eyes patients were finally included. For nAMD and DME, IVC was significantly associated with better visual acuity or best corrected visual acuity improvement and fundus quantitative measures than placebo, laser photocoagulation (LP) or intravitreal triamcinolone acetonide (IVT). However, IVC showed non-inferior efficacy to intravitreal ranibizumab (IVR) according to low quality of evidence, and there was lack of trials comparing the priority of IVC to other anti-VEGF regimens. No definitive increased risk of ocular or non-ocular AEs were observed in study groups. All patients with AEs recovered after symptomatic treatments, and no severe AEs occurred. Patients treated with IVC might have higher quality-of-life scores than that in IVR in nAMD or LP in DME. Additionally, IVC showed cost–utility advantages in nAMD and cost-effectiveness advantages than IVR in pmCNV in China. Conclusions IVC is well-tolerated and effective for improving vision acuity and quantitative measures in fundus condition in patients with nAMD and DME comparing with LP, IVT and placebo, but gains comparable efficacy to IVR. However, well-designed, large-sample and long-term evaluation of IVC shall be conducted in additional studies worldwide.